Cohabitation (Living Together) Among College Students: A Review of Shifting Marital Values ​​and Educational Priorities - Sarah Nur Azizah; Asma Nadia Hasuna; Mirna Nur Alia Abdullah (Lembaga Penelitian dan Pendidikan Mandala, 2026)
This study aims to analyze the phenomenon of declining marriage rates among Generation Z and its impact on population dynamics in Indonesia. In recent years, there has been a growing trend of delayed marriage influenced by various factors, including economic conditions, shifting social values, and the influence of social media. This research employs a qualitative approach with an exploratory design to understand Generation Z’s perspectives on marriage. Data were collected through the analysis of digital content on social media platforms as well as a literature review of scholarly sources and statistical reports. The findings indicate that Generation Z tends to delay marriage due to prioritizing education, career development, and concerns about potential risks in marital relationships. This phenomenon has implications for declining fertility rates, changes in population age structure, and the potential for population aging in the future. From the perspective of the Second Demographic Transition (SDT) theory and the Intermediate Variables of Fertility, these changes reflect a shift from collective- oriented values toward individualization. Therefore, adaptive policies are needed to maintain the balance of population dynamics in Indonesia.